Analysis of Corporate Social Responsibility in oil companies - Doris Liana García Pinargote; Maria Mercedes Bano Hifong; Rosalyn Victoria Cevallos Molina (Universidad Ciencia y Tecnología, 2023)
Corporate Social Responsibility is a strategy used by companies that generate impact on society to achieve a link between the company and stakeholders, creating value and contributing to improving the quality of life. This study analyzed the social responsibility of foreign oil companies operating in Ecuador. The descriptive type, quantitative approach, and non-experimental design methodology were used. The survey was applied as an instrument to a sample of 15 companies, applying the CERES Ethos indicators. The results showed that one company needs to carry out an appropriate social responsibility. Nine companies develop specific corporate social responsibility actions, and five companies have good knowledge of corporate social responsibility. It is concluded that companies have an average of 1.15 indicators, which shows that most perform specific corporate social responsibility actions.